Microsecond Response in Organic Electrochemical Transistors: Exceeding the Ionic Speed Limit. Issue 38 (26th July 2016) - Friedlein, Jacob T.; Donahue, Mary J.; Shaheen, Sean E.; Malliaras, George G.; McLeod, Robert R.
Abstract : Organic electrochemical transistors (OECTs) are transistors that can have extrinsic transconductances as high as 400 S m −1, but they typically have response times on the order of 1 ms or longer. These response speeds are limited by ion transport. It is shown that OECTs can exceed the ionic response speed by a factor of 30 when operated in a high‐speed bias regime.